Efficient electro-assisted adsorption/desorption of phosphate on MOF-derived hierarchically porous carbon electrode. (10th August 2022) - He, Mingming; Zhang, Peng; Zhang, Xueli; Li, Fukuan; Huo, Silu; Fang, Dezhi; Liang, Bolong; Li, Kexun
Abstract: Electro-assisted adsorption (EAA) is an environmentally friendly, effective and economical method for phosphate removal, and its electrosorption capacity is strongly dependent on the electrode material. Herein, we fabricated a MOF-derived hierarchically porous carbon (ZrMC) electrode for the selective electrosorption of phosphate. At 1 V condition, the ZrMC electrode demonstrated a high removal rate of 2.08 mg g −1 min −1 within 40 min, and the maximum electrosorption capability of 163.30 mg g −1 according to Langmuir isothermal model. The excellent performance for phosphate electrosorption was attributed to the hierarchically porous structure, excellent conductivity, and abundant active centers. The electrosorption data was well-fitted with the pseudo-second-order kinetics model. Interestingly, by applying reversed voltage, the ZrMC electrode exhibited an outstanding desorption capacity of 88.33% after ten cycles. Finally, the corresponding electrosorption mechanism was comprehensively clarified by both the Fourier transform infrared spectrometer (FTIR) and X-ray photoelectron spectrometer (XPS) measurements. Our work implies that the ZrMC electrode has a promising potential for highly efficient removal and recovery of phosphate. Graphical abstract: Image 1 Highlights: The ZrMC derived from UiO-66 was utilized in the EAA field for phosphate uptake. The ZrMC showed a high electrosorption rate of 2.08 mg g −1 min −1 at 1 V condition. The ZrMC provided a stable hierarchical structure and well-dispersed active centers. The desorption efficiency maintained more than 88% after ten cycles.